TYPES ACCORDING TO THE STRUCTURE OF THE SENTENCE - Norova Barchinoy Qiyomiddin qizi; Teshaboyeva Nafisa Zubaydulla qizi (Ustozlar uchun, 2023)
ABSTRACT: According to the structure of the studied word, sentence structure and structures, and other word groups used in the sentence, this paper describes the types of sentences used in this manner.